Almost Periodic Solutions for a Second-Order Nonlinear Equation with Mixed Delays. (8th August 2022) - Xu, Mei; Du, Bo
Abstract : This paper is devoted to studying a second-order nonlinear equation with mixed delays. Some sufficient conditions for the existence and exponential stability of the almost periodic solutions are established. The results of this paper extend the existing ones.